2006
DOI: 10.2174/138161206778194079
|View full text |Cite
|
Sign up to set email alerts
|

Hypersensitivity Reactions to Complementary and Alternative Medicine Products

Abstract: Complementary and alternative medicine (CAM) is becoming increasingly popular, and is often used for treating hypersensitivity diseases. Virtually all alternative remedies can cause hypersensitivity reactions, but the most frequently involved ones are tea tree oil, members of the Compositae family, propolis, oils used in aromatherapy, substances responsible for photosensitization, and metal-containing compounds. The main target organ is skin, with manifestations ranging from contact dermatitis (the most common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 71 publications
0
4
2
Order By: Relevance
“…However, in spite of this belief, 16.7% of users referred one or more adverse mucosal and/or cutaneous reactions to herbal products. This percentage was higher than previously observed . The reported adverse effects were described mainly as the occurrence or worsening of distressing symptoms, mainly itching and burning.…”
Section: Discussioncontrasting
confidence: 60%
“…However, in spite of this belief, 16.7% of users referred one or more adverse mucosal and/or cutaneous reactions to herbal products. This percentage was higher than previously observed . The reported adverse effects were described mainly as the occurrence or worsening of distressing symptoms, mainly itching and burning.…”
Section: Discussioncontrasting
confidence: 60%
“…A recent study has also highlighted that the increased DNA methylation predisposes the elderly to respiratory allergic diseases, but could also predispose to HDRs [ 33 ]. The misuse of complementary and alternative medicine and polypharmacy during different degenerative diseases afflicting the elderly is another risk factor for the development of drug allergy [ 34 ]. A recent retrospective survey on 161 hospitalized patients (mean age 63 years) who had an HDR to medications during their hospital stay suggested that the administration of proton pump inhibitors (PPI), used in 83% of hospitalized patients, could favor the occurrence of HDRs, especially to NSAIDs.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the disclosure of CAM use by patients to their healthcare providers is important, especially in the case of phytotherapy. Moreover, the topical use of phytotherapy shows a high potential to provoke type IV hypersensitivity reactions, particularly when using tea tree oil, Compositae, propolis, or metal-containing compounds [38,39]. Photosensitivity is another side effect of phytotherapy, which can appear after oral use (St. John's wort) or topical application, such as aromatherapy (essential oils and bergamot) [40].…”
Section: Discussionmentioning
confidence: 99%